Platinum and palladium on carbon nanotubes: Experimental and theoretical studies - Adjizian, J.; De Marco, Roland; Suarez-Martinez, Irene; El Mel, A.; Synders, R.; Gengler, R.; Rudolf, P.; Ke, X.; Van Tendeloo, G.; Bittencourt, C.; Ewels, C. (Elsevier BV, 2013)
Pristine and oxygen plasma functionalised carbon nanotubes (CNTs) were studied after the evaporation of Pt and Pd atoms. High resolution transmission electron microscopy shows the formation of metal nanoparticles at the CNT surface. Oxygen functional groups grafted by the plasma functionalization act as nucleation sites for metal nanoparticles. Analysis of the C1s core level spectra reveals that there is no covalent bonding between the Pt or Pd atoms and the CNT surface. Unlike other transition metals such as titanium and copper, neither Pd nor Pt show strong oxygen interaction or surface oxygen scavenging behaviour.